Evaluation as a tool for research, learning and making things better - Kalliola, Satu (Cambridge Scholars Publishing, 2014)
This book is one of the first of its kind to bring together a variety of perspectives on evaluation from a multidisciplinary international perspective. The book, with its content derived from leading experts in their chosen fields of practice, illustrates the potential of evaluation to demonstrate the impact and efficiency of social interventions. Examples are given of comparative effectiveness research, realist evaluation, and systematic reviews, as well as of holistic and authentic evaluation, the use of advisory groups, and qualitative needs assessment. The volume also presents some special evaluation tools used by national governments and which are used to influence a variety of professional practices. The key features of the book are: * An international panel of experts sharing the expertise in evaluation. * Multiple perspectives on evaluation theory, methodology and practices articulated through a range of interdisciplinary perspectives. * A primary focus on client-, patient-, and, more generally, human-centredness. * Practical examples of contrasting evaluation methods in use. * Helpful tips and advice offered throughout.The book is compiled from the work of the plenary speakers, plenary panel and selected workshop presentations at the 8th International Conference on Evaluation for Practice, Eval2012, held in Finland in 2012. The contributors come from Australia, Brazil, Finland, Ireland, Italy, Norway, the Republic of Korea, the UK, and the USA.